Potential Utilization of Ipomoea pes-caprae (L.) R. Br. in the Coastal Forest Petanahan Kebumen District - Frita Kusuma Wardhani; Erny Poedjirahajoe (Jurnal Ilmu Kehutanan)
Vegetation that grows in coastal forests has high economic potential, one of which is caused by the high bioactive substances that have pharmacological properties. One species that has high potential as a source of natural medicine is Ipomoea pes-caprae (L.) R. Br. This study aims to examine the potential use of I. pes-caprae in its natural habitat in the coastal forest of Petanahan District, Kebumen Regency. Observations were made using the 1 x 1 meter quadratic method which was placed systematically. The results showed that the area closest to the coast had the highest biomass I. pes-caprae, with an average of 235.01 gr/m2. The distribution of these species is limited by competition and shade. In the pharmacological field, the phytochemical content in Ipomoea pes-caprae extract has high potential to be developed as a drug raw material. But its availability in the coastal forests of Petanahan District is still limited so it cannot be developed to become raw material for natural medicine.